(untitled) (Libya Journal of Geographical Studies, 2024)
The water element in its various aspects, has been present in various social structures of the history of Morocco, and although its organization and management were based on a multicultural social system, and on the objectives and means in the period of the Middle Ages. The trackers of water resources in the Almohad era, they are found from runoff, rivers and valleys, as well as to private wells and water reservoirs, where medieval man devotes all his experiences diligently, creativity and innovation to manage water and ensure its sustainability in the Rahamna zone.